On being and cognition : Ordinatio 1.3 - Duns Scotus, John, approximately 1266-1308 (Medieval philosophy: texts and studies, 2016)
In this book Scotus addresses fundamental issues concerning the limits of human knowledge and the nature of intellect and the object cooperate in generating actual cognition by developing his doctrine of the univocity of being, refuting skepticism and analyzing the way the knowledge in the case of abstractive cognition.